PERSAINGAN USAHA TIDAK SEHAT ANTAR ONLINE SHOP DALAM KONDISI COVID-19 TERHADAP KEBIJAKAN YANG DIKELUARKAN OLEH PRESIDEN - Meria Agustina (Res Judicata, 2020)
In this digital era full of advancement in technology, who is not familiar with the term of online shopping. Nearly the majority of society has taken advantage of today's technological sophistication. The need for online shopping is accommodated by the large numbers of e-commerce sites that have sprung up. Especially since there is a pandemic spread of 2019 Corona Virus Disease or better known as Covid-19. The spread of Covid-19 in Indonesia is also increasing every day, up till now, suspected cases of Covid-19 have been found in 18 provinces. The impact of the panic in the community can be seen through the price of health products such as hand sanitizers which rose unnaturally in online shops. Considering this, there is a lot of competition happens between online shop businesses. Therefore, the writer is interested in analyzing the business competition related to online shops which will affect the stability of the economy in Indonesia, especially, with the consideration of the effects of Social Distancing policy applied by the Government.